Aktual'nost' issledovaniya sporta kak modeli deyatel'nosti cheloveka v ekstremal'nykh usloviyakh v kontekste dikhotomii "vostok-zapad" - Kalmykov, S. V.; Sagaleev, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Research of activity of the human as ethnocultural, ethnopsychological traditions carrier, ability of his adaptation to the market, competition, rivalry, risk, to new socio economic conditions today is very urgent.